Population genomics of emerging Elizabethkingia anophelis pathogens reveals potential outbreak and rapid global dissemination - Shaohua Hu; Hao Xu; Xiaohua Meng; Xiangxiang Bai; Junli Xu; Jinru Ji; Chaoqun Ying; Yunbo Chen; Ping Shen; Yunxiao Zhou; Beiwen Zheng; Yonghong Xiao (Emerging Microbes and Infections, 2022)
Elizabethkingia anophelis is an emerging species and has increasingly been reported to cause life-threatening infections and even outbreaks in humans. Nevertheless, there is little data regarding the E. anophelis geographical distribution, phylogenetic structure, and transmission across the globe, especially in Asia. We utilize whole-genome sequencing (WGS) data to define a global population framework, phylogenetic structure, geographical distribution, and transmission evaluation of E. anophelis pathogens. The geographical distribution diagram revealed the emerging pathogenic bacteria already distributed in various countries worldwide, especially in the USA and China. Strikingly, phylogenetic analysis showed a part of our China original E. anophelis shared the same ancestor with the USA outbreak strain, which implies the possibility of localized outbreaks and global spread. These closer related strains also contained ICEEaI, which might insert into a disrupted DNA repair mutY gene and made the strain more liable to mutation and outbreak infection. BEAST analysis showed that the most recent common ancestor for ICEEaI E. anophelis was dated twelve years ago, and China might be the most likely recent source of this bacteria. Our study sheds light on the potential possibility of E. anophelis causing the large-scale outbreak and rapid global dissemination. Continued genomic surveillance of the dynamics of E. anophelis populations will generate further knowledge for optimizing future prevent global outbreak infections.